Lifestyle Modification-Improving Systemic Athero-Protective Factor, Circulating Pentraxin 3, in High-Risk Patients with Metabolic Syndrome - Tojo, Taiki; Yamaoka-Tojo, Minako (Cardiology and Cardiovascular Medicine, 2021)
Background: Metabolic syndrome (MetS) is associated with an increased risk of developing atherosclerotic cardiovascular diseases (CVD). C-reactive protein (CRP) and serum amyloid protein are recognized as classic short pentraxins, whereas pentraxin 3 (PTX3) belongs to the long pentraxins. PTX3 is an acute phase protein, which is strongly expressed by advanced atherosclerosis lesions as a primary inflammatory response in association with macrophage and neutrophil infiltration. We hypothesized that circulating PTX3 could be a useful biomarker to enhance the effects of lifestyle modification on systemic inflammation in patients with MetS. Methods: To examine the relationship between circulating PTX3 and MetS risk scores, we measured circulating PTX3 in 86 high-risk cardiovascular disease patients with or without MetS before and after lifestyle modification. Circulating levels of PTX3 were measured using ELISA. Results: All subjects had similar reductions in weight, waist circumference, and blood pressure. Circulating PTX3 was significantly decreased in MetS patients (P < 0.001) and was inversely correlated with the accumulation of MetS risk scores (r = -0.533, P < 0.001), and was correlated with high-density lipoprotein (HDL) cholesterol, the presence of diabetes mellitus, and white cell count, but not with waist circumference, body mass index (BMI), or CRP. An increase in PTX3 levels were significantly correlated with the levels of baseline BMI, waist circumference, circulating PTX3 concentration, and MetS risk scores. Conclusions: Lifestyle modification increased circulating levels of PTX3 in relation to the accumulation of MetS risk scores in high-risk patients with MetS, who have reduced levels of PTX3, independent of CRP. These data suggest that circulating PTX3 may be an effective novel biomarker that helps to predict the effectiveness o